Implementasi Pembelajaran Terpadu dalam Mengembangkan Kreativitas Siswa Sekolah Dasar - Safitri, Anita; Elistantia, Eliga; Pinanda, Lula; Arrosyad, M. Iqbal (JBES (Journal Basic Education Skills), 2023)
The application of integrated learning to develop the creativity of elementary school students through an approach that integrates several subjects into one related learning topic. The purpose of this study was to determine the effectiveness of integrated learning in increasing the creativity of elementary school students. This study used a qualitative method with a library research approach. The results showed that there were two major themes studied. The theme is the implementation of integrated learning and student creativity.